ВОВЕДНИ БЕЛЕШКИ ЗА ХРВАТСКАТА ОПШТИНСКА ХЕРАЛДИКА И ВЕКСИЛОЛОГИЈА / SOME INTRODUCTORY NOTES ON CROATIAN MUNICIPAL HERALDRY AND VEXILLOLOGY - Zeljko Heimer (Македонски хералд - Macedonian Herald, 2019)
The paper presents an overview ofhistory and the current state of Croatianofficial municipal heraldry and vexillology.It provides a brief overview of its historicaldevelopment, providing the basisof the heraldic restoration which beganin the mid-1990s. It presents the currentlegislation and regulations and the proceduresinvolving the design, adoption,and approval of municipal coats of arms andflags, highlighting some particular phenomenaappearing in their use, such as the ceremonialflags. It analyses the number of adopted and approvedsymbols in use in Croatia.